COVID-19 and financial markets: Assessing the impact of the coronavirus on the eurozone - Paola D'Orazio; Maximilian W. Dirks (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
COVID-19 has quickly emerged as a novel risk, generating feverish behavior among investors, and posing unprecedented challenges for policymakers. The empirical analysis provides evidence for a significant negative effect on stock markets of COVID-19-related measures announced in the Euro Area from January 1st, 2020 to May 17th, 2020. Further negative effects are detected for movements in bond yields, EU volatility index, Google trends, and infection rates. Health measures have, instead, a significant positive effect, while fiscal policy announcements are not significant. – – COVID-19 hat sich schnell zu einem neuartigen Risiko entwickelt, das bei Investoren ein nervöses Verhalten hervorruft und die politischen Entscheidungsträger vor beispiellose Herausforderungen stellt. Die empirische Analyse findet einen signifikanten negativen Effekt auf Aktienmärkte durch auf COVID-19 bezogene Politikmaßnahmen, die in der Eurozone zwischen dem 1. Januar 2020 und dem 17. Mai 2020 erlassen wurden. Darüber hinaus kann ein negativer Zusammenhang zwischen Aktienmärkten und Anleiherenditen, dem EU-Volatilitätsindex, Google-Trends-Daten und Infektionszahlen festgestellt werden. Während für Gesundheitsmaßnahmen ein signifikanter positiver Effekt gefunden wurde, waren fiskalpolitische Ankündigungen nicht signifikant.
Keywords: E44; G15; 330; Coronavirus; COVID-19; investor behavior; stock market volatility; containment policies; policy announcements; fiscal policy